2006
DOI: 10.3354/meps320185
|View full text |Cite
|
Sign up to set email alerts
|

Symbiont abundance in thyasirids (Bivalvia) is related to particulate food and sulphide availability

Abstract: Many bivalve species with chemoautotrophic symbionts have mixotrophic diets and some of their nutritional requirements are met by particulate feeding. The symbionts require reduced compounds (such as sulphide) for their autotrophic production. As the concentration of both particulate food and sulphide can vary in their habitat, it has been suggested that symbiont numbers may vary in response. To address whether symbiont abundance can be influenced by the external medium, we compared symbiont abundance (1) in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…There was also a similar symbiont decline in thyasirid species and bathymodiolines after starvation in seawater devoid of sulfide or while kept under controlled conditions along with particle feeding (20,40). The conditions in this study were more drastic for the host and its symbionts because no particle feeding was allowed for the host and no sulfide was available as an energy source for the symbionts.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…There was also a similar symbiont decline in thyasirid species and bathymodiolines after starvation in seawater devoid of sulfide or while kept under controlled conditions along with particle feeding (20,40). The conditions in this study were more drastic for the host and its symbionts because no particle feeding was allowed for the host and no sulfide was available as an energy source for the symbionts.…”
Section: Discussionmentioning
confidence: 77%
“…Apart from the decrease in symbiont abundance suggested by transmission electron microscopy (TEM) analysis and a decrease in sulfur and protein content in the gill tissue of thyasirids (20,38,40), little is known about the physiological status of these symbionts and the changes undergone by the symbiotic population of starved bivalves. A previous study of the population was carried out under natural conditions with Codakia orbicularis, a chemoautotrophic bivalve.…”
mentioning
confidence: 99%
“…Consequently, analysis of δ 13 C signatures of host tissues revealed that the relative importance of particulatederived nutrition in chemosymbiotic bivalves can vary be tween 2 and 74% (Cary et al 1989, Conway et al 1989, Dando & Spiro 1993, Rossi et al 2013. This flexible feeding mode may help chemosymbiotic bivalves survive in environments where the concentration of particulate food, sulphide and oxygen varies in space and/or in time (Dufour & Felbeck 2006, van Gils et al 2012, Rossi et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…This has been demonstrated in vent and seep Mytilidae, in which relative amounts of sulfur-versus methane-oxidizing bacteria reflect the availability of their respective substrates, and can also display age-or time-related variations (Le Fiala-Médioni et al, 2002;Halary et al, 2008;Riou et al, 2008). Although they only have sulfur-oxidizing bacteria, Thyasiridae can also display inter-habitat variability in symbiont densities, with higher densities when sulfide is more abundant in the environment (Dufour and Felbeck, 2006). Using carbon stable isotopes ratios, Dando and Spiro (1993) have shown that the contribution of chemoautotrophic bacteria could vary inter-annually in Thyasira sarsi and T. equalis, in relation to environmental change in the habitat.…”
Section: Ecological Trends In Bivalve Symbiosesmentioning
confidence: 99%
“…Symbiont chemoautotrophy is supported by the occurrence of APS reductase-encoding genes in symbionts of some species , and by the carbon stable isotope signatures of animal tissue that are in the range of values measured in chemosymbiotic metazoans harboring sulfur-oxidizing symbionts. Variability in symbiont abundances and the host nutritional strategy depends upon environmental conditions (presence of sulfide and particles), as shown in Thyasira flexuosa, T. sarsi and Parathyasira equalis, confirming their ability to withstand fluctuating environments (Dando and Spiro, 1993;Dufour and Felbeck, 2006). Symbiosis has been investigated in 9 identified species from coastal and deep sediment, including cold seeps, but molecular data on symbionts remain very scarce (Table 1).…”
Section: Thyasiridaementioning
confidence: 99%